2015
DOI: 10.1002/adma.201500546
|View full text |Cite
|
Sign up to set email alerts
|

The Hydric Effect in Inorganic Nanomaterials for Nanoelectronics and Energy Applications

Abstract: Protons, as one of the world's smallest ions, are able to trigger the charge effect without obvious lattice expansion inside inorganic materials, offering a unique and important test-bed for controlling their diverse functionalities. Arising from the high chemical reactivity of hydrogen (easily losing an electron) with various main group anions (easily accepting a proton), the hydric effect provides a convenient and environmentally benign route to bring about fascinating new physicochemical properties, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 139 publications
(203 reference statements)
2
43
0
1
Order By: Relevance
“…It has been demonstrated that Co acts as an effective promoter to enhance the catalytic activity of MoS x [17]; however, such CoMoS x catalyst film electrodeposited on a planar electrode still requires an overpotential of 200 mV to drive 1.04 mA•cm -2 . Recent studies have demonstrated that the direct nanoarray growth of an active phase on a current collector provides distinct advantages, including higher electrode stability, lower series resistance, exposure of more active sites, and easier electrolyte and gas diffusion [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Thus, although it has not been reported to date, the development of a CoMoS x nanoarray as a three-dimensional (3D) catalyst electrode is highly attractive for achieving high-efficiency hydrogen evolution catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that Co acts as an effective promoter to enhance the catalytic activity of MoS x [17]; however, such CoMoS x catalyst film electrodeposited on a planar electrode still requires an overpotential of 200 mV to drive 1.04 mA•cm -2 . Recent studies have demonstrated that the direct nanoarray growth of an active phase on a current collector provides distinct advantages, including higher electrode stability, lower series resistance, exposure of more active sites, and easier electrolyte and gas diffusion [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Thus, although it has not been reported to date, the development of a CoMoS x nanoarray as a three-dimensional (3D) catalyst electrode is highly attractive for achieving high-efficiency hydrogen evolution catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, surface OVs can enhance the electron transfer from O-vacancies to metal d band to further effectively tune the adsorption of surface species for catalysis. [40][41][42] For example, Chen et al investigated the influence of OVs on the oxygen electrocatalysis of rutile-type β-MnO 2 by introducing intrinsic OVs without modification by foreign additives. [42] They found that OVs-containing oxide demonstrates a more positive potential, larger current and lower peroxide production for ORR catalysis, and also promotes OER catalysis.…”
Section: Defect Engineeringmentioning
confidence: 99%
“…H, due to its small size, is able to migrate in many inorganic compounds and can occupy interstitial sites without large structural expansion. It is able to induce intrinsic defects that provide free electrons1213, modify the band gap14, interact with O vacancies1516, and induce insulator-to-conductor transitions17. Despite much progress, H doping therefore remains a challenge to metal oxide semiconductors.…”
mentioning
confidence: 99%